Modeling of Self-Vibratory Drilling Head-Spindle System for Predictions of Bearings Lifespan. (21st August 2011) - Forestier, F.; Gagnol, V.; Ray, P.; Paris, H.
Abstract : The machining of deep holes is limited due to inadequate chip evacuation, which induces tool breakage. To limit this drawback, retreat cycles and lubrication are used. An alternative response to the evacuation problem is based on high-speed vibratory drilling. A specific tool holder induces axial self-maintained vibration of the drill, which enables the chips to be split. The chips are thus of a small size and can be evacuated. To anticipate the potential risk of decreased spindle lifespan associated with these vibrations, a model of the behavior of the system (spindle—self-vibrating drilling head—tool) is elaborated. In order to assess the dynamic behavior of the system, this study develops a rotor-based finite element model, integrated with the modelling of component interfaces. The current results indicate that the simulations are consistent with the experimental measurements. The influence of spindle speed and feed rate on bearing lifespan is highlighted.